DISASSEMBLY OF CONNECTING THREADS USING VIBROWAVE TECHNIQUE UNDER REPAIR AND UTILIZATION OF ENGINEERING PRODUCTS - Anatoly Prokofyevich Babichev; Dieudonné Essola; Sergey Nikolayevich Khudoley (Advanced Engineering Research)
The possibility of the vibrowave impact application under the connecting threads disassembly is investigated. The specified operations go to make up a considerable amount of work in the repair and recycling of engineering products. It is essential to find the problem solution to restrict the environment pollution, to economize natural and material resources, energy, to shorten time and means in the production of new goods. Vibrowave loading is performed in the following manner. A solid iron rod – wave duct vibrates. These oscillations (15–50 Hz) stimulate the torque reduction under the connection disassembly. The torque reduction under processing similar water-cured connections with a variety of time intervals is considered. The obtained results are compared and analyzed. The data characterizing the interrelation between the working diagram of the vibrowave impact on the connection elements, target exposure time, and disassembly efficiency is offered.